METABOLIC SYNDROME TRAITS IN UROLITHIASIS PATIENTS - Aritonang, Johannes; Ali, Zulfikar (Indonesian Urological Association, 2020)
Objective: To explore the relation of MetS and urolithiasis in our center. Material & Methods: This is a prospective study of all patients diagnosed with urolithiasis in Kardinah Hospital, Tegal, from April to June 2018, who were screened for metabolic syndrome criteria. The data was collected from the medical record and analyzed with SPSS ver. 23. Results: We included 71 cases of urinary tract stone in our center. 8.4% of the patients didn’t undergo definitive therapy for stones caused by patients’ preferences or the surgery being postponed with various reasons. The patient's mean age is 54.7 ± 11.24, with a male to female ratio 2.4:1. The average BMI is 20.9 ± 2.3 kg/m2. Most of the stones are found in kidney (38.0%) and bladder (26.8%). The average blood pressure is 127.2 ± 7.96 mmHg for systolic pressure and 81.6 ± 5.77 mmHg for diastolic pressure. The average values of lipid profile include total cholesterol, high- and low-density lipoprotein, and triglyceride were 177.0 ± 35.92, 52.0 (27-96), 107.3 ± 37.58 and 131 (50-406), respectively. The mean of patient’s blood glucose level is 122 mg/dL, and the highest level is 203 mg/dL. Conclusion: Not all of the MetS traits found in our patients in Kardinah Hospital. The HDL level is the only variable that shown abnormal level and it could be included into one of the MetS criteria of diagnosis. Thus, this observational study needs further research to confirm the correlation between urolithiasis and MetS, and also the underlying mechanism.